Contents and composition of individual phospholipid classes from biceps femoris related to the rearing system in Iberian pig. (15th February 2021) - Tejeda, Juan F.; Gandemer, Gilles; García, Carmen; Viau, Michelle; Antequera, Teresa
Highlights: Phospholipid individual class contents are highly influenced by rearing system. Large enclosures allocated to Montanera pigs increase phospholipid class contents. Montanera system affects fatty acid composition in the main phospholipid classes. Dimethylacetal composition of phospholipids is influenced by rearing system. Abstract: During dry-cured ham processing, phospholipids (PL) are the main substrates of lipolysis and oxidation. However, the published data on individual PL classes in the pig muscle are inconsistent. This study determined the PL class contents and composition in biceps femoris of Iberian pigs according to the rearing system ( Montanera vs Pienso ). Phosphatidylcholine (PC), phosphatidylethanolamine (PE), cardiolipin (CL) and sphingomyelin contents were higher in the Montanera pigs than in the Pienso pigs. Total PL and PC, PE, phosphatidylinositol + phosphatidylserine and CL contained higher levels of oleic acid and slightly higher levels of n-3 polyunsaturated fatty acids (PUFA) but lower levels of n-6 PUFA in the Montanera pigs than in the Pienso pigs. The rearing system had no effect on the plasmalogen content but influenced aldehyde composition, mainly in PE and in total PL. These results can partially explain the differences in sensory properties of dry-cured ham between the Montanera and Pienso systems .